2021
DOI: 10.1186/s12864-021-07467-8
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast genome sequence of Chongming lima bean (Phaseolus lunatus L.) and comparative analyses with other legume chloroplast genomes

Abstract: Background Lima bean (Phaseolus lunatus L.) is a member of subfamily Phaseolinae belonging to the family Leguminosae and an important source of plant proteins for the human diet. As we all know, lima beans have important economic value and great diversity. However, our knowledge of the chloroplast genome level of lima beans is limited. Results The chloroplast genome of lima bean was obtained by Illumina sequencing technology for the first time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…This might suggest that the rpl16 gene went through a great mutation that was crucial to the evolution process of Litsea species. Although studies have reported rpl16 to be one of the highly divergent genes [ 59 ] and a positive selection site [ 60 ], as unique and significant as the present study is this is not a common in studies of other angiosperms. The other positive selection site, the ycf2 gene, was more commonly described in previous studies [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 54%
“…This might suggest that the rpl16 gene went through a great mutation that was crucial to the evolution process of Litsea species. Although studies have reported rpl16 to be one of the highly divergent genes [ 59 ] and a positive selection site [ 60 ], as unique and significant as the present study is this is not a common in studies of other angiosperms. The other positive selection site, the ycf2 gene, was more commonly described in previous studies [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 54%
“…However, in the three control groups, the Ka/Ks ratios of the ndhD, rpoA, and ndhF genes were greater than one, which showed that the three genes of F. longipetiolata were positively selected to adapt to the living environment. Positive selection of ndhD (Pterocarpus and Leguminosae) [50,72], rpoA (Trifolium alexandrinum and Trifolium resupinatum), and ndhF (T. alexandrinum, T. resupinatum and Cardamine genus) [73,74] genes has also been reported in previous studies. It is also reported that NADPH dehydrogenase genes (ndhD and ndhA) tend to evolve at a higher rate than other genes [75].…”
Section: Discussionmentioning
confidence: 60%
“…the cp genome of R. gelida, reflecting the fact that Rhodiola chloroplast genomes exhibited a significant difference in type, length and number of repeats. Chloroplast SSR markers are efficient genetic resources to investigate population genetics and biogeography of closely related taxa due to their relatively richness, high reproducibility and polymorphism [38,39]. Wang et al used 11 ISSR primers to reveal the interspecific or intraspecific genetic differences and diversity of four Rhodiola species [9].In our study, A and T nucleotides were the most common, while tandem G or C repeats were quite rare (Fig.…”
Section: Discussionmentioning
confidence: 65%